MAIN PROBLEMS OF DYNAMICALLY STRUCTURED ENTERPRISE MANAGEMENT UNDER PRESENT RUSSIAN CONDITIONS - A. S. Lankin (Модернизация, инновация, развитие, 2016)
In their activity, minor and medium enterprises come across various problems. Clusters provide best conditions for such enterprises to operate. Among main Russian clusters’ management problems there are: multistage management system; absence of a single and transparent accounting and budgeting system; vague distribution of responsibilities between the managing company and business units; inadequate horizontal links between business units; management process inadequate decentralization. Typical group problems’ causes are examined, solution ways and means are proposed.